THE USE OF SIMULATION MODELLING IN THE TRAINING OF SHIP NAVIGATORS: THE INFLUENCE OF EXTERNAL FACTORS ON THE CHARACTERISTICS OF SHIP MOVEMENT - Zaytseva Тетяна; Kravtsova Людмила; Tereshchenkova Оксана (Journal of Information Technologies in Education (ITE), 2021)
Being competent means to take into account all the circumstances of the situation and to adequately use the acquired knowledge and experience. Competence allows a person to be well-informed not only about the normal course of events but also in emergencies. It also allows to turn person’s experience into his own values and attitudes. Among the tasks facing higher education, one of the main places is the formation of key competencies, the level of formation of which is judged on the quality of educational content. The main distinguishing feature of the competency-based approach is that it has activity-orientated nature, where the criterion of competence is the achievement of a positive result by the student. At Kherson State Maritime Academy the 1st year program of "Information Technologies" discipline contains "Information Technologies in Navigation" module, which examines the algorithms and methods of solving professional problems. This content of the course contributes to improving the quality of training of future ship navigators, and implementing the focus of this discipline on their professional activities. In other words, we begin to form both subject and universal professionally oriented competencies. Specially selected tasks acquaint cadets with information technology in terms of implementing the solution of professionally oriented tasks, namely: 1) construction of mathematical (information) models; 2) implementation of mathematical models of problems by means of MS Excel; 3) analysis of possible solutions of the problem; 4) optimization of technological processes, taking into account all possible situations and methods of decision making. Under the key competencies we will understand not only the system of expertise, knowledge and skills, but also the ability of future professionals to use this system for professional activities. This article proposes methodological techniques for the formation of subject professionally oriented competencies of future ship navigators. These techniques are shown on the example of solving an applied problem using an information-modeling approach to the analysis and risk assessment of a ship operating in conditions of changing or unpredictable external influences. These influences are one of the factors that can lead to emergencies.